Halamphora daochengensis sp. nov., a new freshwater diatom species (Bacillariophyceae) from a small mountain lake, Sichuan Province, China - ZHANG, WEI; WANG, TING; LEVKOV, ZLATKO; JÜTTNER, INGRID; ECTOR, LUC; ZHOU, QI-CHAO (Magnolia Press, 2019)
During a survey of freshwater diatoms from a mountain lake, Lake Congqiancuo, Haizishan Nature Reserve, Yading, Daocheng County, Sichuan Province, China, a new Halamphora species, Halamphora daochengensis sp. nov. was found. A detailed morphological description of the new species is presented, based on light and scanning electron microscopy. The main features of H. daochengensis are dorsiventral, semi-lanceolate valves with a strongly triundulate dorsal margin and valve ends distinctly protracted and capitate. The new species is compared with other similar species including Halamphora dusenii and H. normanii var. undulata which differ in size, valve shape, stria density and ultrastructure.
Keywords: taxonomy, new species, Halamphora, Lake Congqiancuo, Haizishan Nature Reserve, Asia, Algae